INTENSITAS PENGGUNAAN SMARTPHONE DAN RISIKO TERJADINYA DE QUERVAIN’S SYNDROME KEPADA MAHASISWA FAKULTAS ILMU KOMPUTER DI UNIVERSITAS KLABAT - Caroline, Anggryani; Pitoy, Frendy Fernando (Klabat Journal of Nursing, 2025)
The intensity of smartphone use has been considered as one of the risk factors for developing De Quervain’s Syndrome, a condition caused by repetitive hand movements leading to inflammation of the wrist tendons. This study aimed to determine the relationship between smartphone usage intensity and the risk of De Quervain’s Syndrome among students of the Faculty of Computer Science at Universitas Klabat. A cross-sectional design was applied with statistical analysis using Spearman’s rho correlation and ordinal logistic regression. A total of 244 participants were recruited based on the Slovin formula with an additional 10% attrition rate. Research instruments included the De Quervain Screening Tool (DQST) and a smartphone usage intensity questionnaire. The results indicated that most participants had a high level of smartphone usage (88.5%), while the majority presented a low risk of De Quervain’s Syndrome in the right hand (43.4%) and in the left hand (42.2%). Statistical analysis showed p values of 0.791 for the right hand and 0.600 for the left hand, indicating no significant relationship between smartphone usage intensity and the risk of De Quervain’s Syndrome. Logistic regression analysis also revealed that the alpha values of all smartphone usage variables were >0.05, suggesting no partial effect on the risk. This study recommends that students use smartphones more wisely to prevent health problems and encourages further research to investigate other contributing factors related to intensive smartphone use. Intensitas penggunaan smartphone merupakan salah satu faktor risiko yang dapat memicu terjadinya De Quervain Syndrome akibat gerakan berulang yang menyebabkan peradangan pada tendon pergelangan tangan. Penelitian ini bertujuan untuk mengetahui hubungan antara intensitas penggunaan smartphone dan risiko terjadinya De Quervain Syndrome pada mahasiswa Fakultas Ilmu Komputer Universitas Klabat. Penelitian menggunakan desain cross sectional dengan uji Spearman’s rho correlation dan ordinal logistic regression. Sebanyak 244 partisipan ditentukan melalui perhitungan rumus Slovin dengan tambahan 10% attrition rate. Instrumen penelitian berupa kuesioner De Quervain Screening Tool (DQST) dan kuesioner intensitas penggunaan smartphone. Hasil menunjukkan sebagian besar partisipan memiliki intensitas penggunaan smartphone tinggi (88,5%), serta risiko rendah untuk tangan kanan (43,4%) maupun tangan kiri (42,2%). Analisis statistik memperoleh p value tangan kanan (p=0,791) dan tangan kiri (p=0,600), sehingga tidak terdapat hubungan signifikan antara intensitas penggunaan smartphone dan risiko De Quervain Syndrome. Uji regresi logistik juga menunjukkan nilai alpha dari seluruh variabel >0,05 yang berarti tidak berpengaruh secara parsial terhadap risiko. Penelitian ini menyarankan mahasiswa agar lebih bijaksana menggunakan smartphone untuk mencegah masalah kesehatan, serta mendorong penelitian selanjutnya meninjau faktor lain yang mungkin berhubungan dengan penggunaan smartphone intensitas tinggi.